A young patient with heart failure was diagnosed with extra-adrenal paraganglioma: a case report - Jing Zhang; Lihua Cao; Lina Yan; Cong Jin; Dan Zhang (BMC Cardiovascular Disorders, 2022)
Abstract Background We present a case of pelvic paraganglioma that presented with heart failure as the primary symptom. Case presentation A 35-year-old man was admitted to hospital due to heart failure. Contrast-enhanced pelvic CT showed mass shadows in the posterior wall of the bladder and multiple enlarged lymph nodes in the retroperitoneal area. Ultrasound-guided puncture was performed, and the pathologic diagnosis was extra-adrenal paraganglioma. The patient refused any chemotherapy and died within six months of diagnosis. Conclusion The possibility of neuroendocrine-related tumors, for example paragangliomas, should be considered in young patients with heart failure, especially those with concomitant hypertension and diabetes.